Development and validation of a scale for safety climate measurement at workgroup level - Soares, Helena Raquel dos Santos (2019)
In Portugal, construction and manufacturing are two of the sectors with higher injury rates. In these industries several workers operate in teams. In this kind of arrangements, the team leader/supervisor and co-workers play an important role in what regards to occupational safety. As a result, safety performance should not be only analyzed at organizational level but also at the group level, being safety climate scales good instruments to this end. Since were found very few empirical research that described and validated scales to measure safety climate at workgroup level, this study aims to validate an instrument for that purpose. Additionally, relationships between workgroup safety climate and other variables, such as safety behaviors, accident rates and organizational safety climate were stablished. It was measured organizational safety climate, group safety climate, safety behaviors and injury frequency rates at workgroup level. The group safety climate included two subscales: leader safety climate and co-worker safety climate. The sample was composed by 207 workers from 3 different companies of the construction and manufacturing sectors. Exploratory and confirmatory factor analysis and correlations with other variables was used to validate the scales measuring the constructs under study. Results confirmed a single dimension for organizational safety climate and a two-factor structure for group safety climate, i.e., group leader safety climate and group co-worker safety climate. The group safety climate was positively correlated with organizational safety climate and safety behaviors at individual level. At workgroup level, when aggregated data was used, relationships with behaviors were only significant for safety participation dimension. This study contributed to the current knowledge about safety climate and the scale should be used by OSH practitioners as a proactive safety indicator.